Knowledge Required for Integrated Learning Management - Susakaro, Phrakrupalad Prapan (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 10 No 2 (2018): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2018)
The integrated learning management for Thai language requires a science that means multiple knowledge and selection arts to combine any sciences to be good parts of learning management which has a consistent relationship in order that learners will get holistic knowledge and experience in cognitive domain, psychomotor domain, and mind affective domain. Knowledge that requires for integrated learning management is about the present version of basic educational curriculum, about contents in learning management, about teaching principles, teaching method, teaching techniques and teaching forms suitable for integrated learning management, about activity design in learning management and atmospheric creation with learner centered learning, about creating along with using teaching media, about searching learning sources, about learning measure as well as evaluation, about writing plans of learning management, and any other inclusive ones such as, educational philosophy, professional ethics, psychology for children, spirits of teachers.